2021
DOI: 10.3390/ijerph18094832
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Perceived Physical Fitness during the COVID-19 Epidemic: A Population of 40- to 69-Year-Olds in Japan

Abstract: The COVID-19 pandemic has caused an abrupt change in lifestyle for many people with restrictions, often leading to a decrease in physical activity (PA), and thus contributing to a negative perception of health status. The purpose of this study was to examine the effects of the COVID-19 epidemic on physical activity and perceived physical fitness in Japanese adults aged 40 to 69 years. Data were collected from an online survey conducted between October 19 and 28, 2020. The analytic sample consisted of 1989 Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Previous studies have shown a similar trend in outing and walking behaviors ( Adachi et al, 2021 , Hanibuchi et al, 2021 , Hino and Asami, 2021 ), and this could be attributed to more walks for daily activities before the pandemic among younger individuals and residents in urban area, thereby resulting in a significant decrease in the number of steps. Additionally, sedentary behavior clearly increased among females, similar to previous reports that showed that females became inactive during the outbreak in Japan ( Hanibuchi et al, 2021 , Hino and Asami, 2021 , Makizako et al, 2021 ). Containment measures such as school closure or self-isolation may have increased the burden of housework on females ( Hanibuchi et al, 2021 , Power, 2020 ), making them more inactive.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Previous studies have shown a similar trend in outing and walking behaviors ( Adachi et al, 2021 , Hanibuchi et al, 2021 , Hino and Asami, 2021 ), and this could be attributed to more walks for daily activities before the pandemic among younger individuals and residents in urban area, thereby resulting in a significant decrease in the number of steps. Additionally, sedentary behavior clearly increased among females, similar to previous reports that showed that females became inactive during the outbreak in Japan ( Hanibuchi et al, 2021 , Hino and Asami, 2021 , Makizako et al, 2021 ). Containment measures such as school closure or self-isolation may have increased the burden of housework on females ( Hanibuchi et al, 2021 , Power, 2020 ), making them more inactive.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have documented decreased physical activity during the COVID-19 outbreak in Japan ( Adachi et al, 2021 , Hino and Asami, 2021 , Makizako et al, 2021 , Yamada et al, 2020 ). However, to the best of our knowledge, this is the first study to examine the association of changes in physical activity during the COVID-19 outbreak in Japan with the demographic, socioeconomic, and geographical attributes, and changes in work situation and perception of anxiety, simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 continued to be a global issue in 2021 [ 1 ]. The COVID-19 pandemic caused changes in lifestyle and health behavior, such as physical inactivity and sedentary behavior, among people of all ages, including university students, middle-aged adults, and older adults [ 2 , 3 , 4 ]. Sustained physical inactivity due to the COVID-19 pandemic has a negative impact on future health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Responders who reported a history of stroke, Parkinson disease, dementia, depression, and/or other neurological disorders known to influence reduced PA and cognitive impairment were excluded. [ 23 , 24 ] In addition, based on a previous study, [ 24 ] responders who reported more than 960 min/day or 0 min/day of total PA time and more than a tenfold change (increasing or decreasing) in total PA were also excluded. Finally, data from 1967 middle-aged and older Japanese adults were analyzed.…”
Section: Methodsmentioning
confidence: 99%